Unconventional monetary policy and bank risk-taking in the euro area - Jörg Schmidt (Philipps-University Marburg, School of Business and Economics, 2018)
This paper studies risk-taking by European banks. We construct a measure of risk-taking which relates changes in three month ahead expected credit standards for several non-financial private sector categories to risk of the macroeconomic environment banks operate in to reflect whether credit standards react disproportionately to changes in the monetary policy stance. We use an estimated bond market based measure to assess the overall riskiness prevailing in the economy. With this approach we shed some light on whether banks act excessively risky and provide new evidence as well as an alternative assessment on the amplifying nature of the risk-taking channel of monetary policy. We include our measure in a VAR in which structural innovations are identified with sign restrictions. The key outcomes of this paper are the following: Restrictive (expansionary) monetary policy shocks increase (decrease) our measure of risk-taking. Increases (decreases) in our measure are caused by disproportionately strong (weak) reactions in credit standards compared to the overall macroeconomic risk, especially during the recent financial crisis. Disproportionately in the sense that our macroeconomic risk measure is less affected by restrictive (expansionary) monetary policy shocks than credit standards. We conclude that expansionary monetary policy shifts the portfolio of banks to overall riskier asset holdings. The credit granting reaction depends on the category: In general, credit to non-financial corporations are less sensitive to monetary policy shocks while mortgages seem to be affected.
Keywords: E44; E52; G12; 330; monetary policy; euro area; bank risk-taking; credit standards; sign restrictions VAR